P1-S6.09 An audit of management of prenatal syphilis serology in the STI Clinic, Calgary, AB, Canada. (10th July 2011) - Chu, A; Read, R; Scarrott, R
Abstract : Background: Outbreaks of syphilis have been occurring across Canada since 2001, with the province of Alberta having the 2nd highest incidence in 2007. As a result, there has been a national increase in the number of reported congenital cases. Current Canadian guidelines recommend performing syphilis serology at the 1st prenatal visit with rescreening at 28–32 weeks gestation, and at delivery in high-risk women. In our center, any positive syphilis serology is referred to the Calgary STI Clinic for staging and treatment recommendations. This is an internal audit of positive prenatal syphilis serologies from 2009 to 2010. Methods: Charts from pregnant women with a positive prenatal syphilis serology, defined as a positive or indeterminate syphilis EIA, from 1 January 2009 to 31 December 2010 were retrospectively reviewed. Syphilis staging was performed by the Medical Director according to national criteria. Results: 48 charts were reviewed: 9 were staged as biological false positives, 22 were previously adequately treated women with low or negative RPR titres not suggestive of reinfection, 13 were late latent (LL) treated with 7.2 μ of benzathine penicillin (PCN), and 4 were early latent (EL) treated with 2.4 μ of benzathine PCN. The mean number of days it took from receipt of a positive serology to contacting the patient were 9.8, 10.2, 2.3, and 1.8, respectively. The mean time to 1st dose of PCN was 8.8 for EL and 17.8 for LL (see Abstract P1-S6.09 table 1 ). There was 1 case of congenital syphilis in an infant whose mother presented in labour with no prenatal care-her RPR was 1:256. 1 woman with an RPR titre of 1:128 was treated with benzathine PCN 1 week before her estimated date of delivery. She went into preterm labour the afternoon post-injection; it is unclear whether or not the injection induced preterm labour. Her twins were treated with iv PCN with no adverse outcomes. Conclusions: Routine prenatal syphilis screening has identified 14/48 women who required PCN treatment, all of whom received PCN prior to delivery with only 1 woman experiencing a possible adverse event. The only congenital case occurred in a mother with no prenatal care, suggesting a need for a strategy to identify marginalised women with syphilis early in pregnancy. Although the average time to contact these patients was short, the time to administration of 1st dose of PCN was longer, reflecting the need to educate women about the importance of prompt and complete therapy in preventing congenital syphilis.